RELEVANSI NILAI ARUS KAS OPERASI TERHADAP UNEXPECTED RETURN STUDI DI BURSA EFEK JAKARTA - CHARLES DICKENS GULTOM (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 1999)
The value-relevance of cash flow from operations, as reported under PSAK No. 2, is the object to be examined in this paper. The value-relevance is to be assessed by the cash flow from operations disclosures influencing the investment decisions. The stock price changes arround the announcement date represents the investment decisions. The results show that actual cash flow from operation have incremental value-relevance beyond earning. But we found that significance of cash flow from operations is not better than earning. The second issue, we examine the value-relevance of estimated cash flow from operations. The estimates that readily available from balance sheet and financial statement data. The results show that estimated cash flow from operation have incremental value-relevance beyond earning. But the estimates have no significance when the actual cash flow from operations significance better than estimates. This result suggests that cash flow from operation, as reported under PSAK No.2, should have substituted the role of estimated cash flow for investment decision making.